2020
DOI: 10.3390/fermentation6010034
|View full text |Cite
|
Sign up to set email alerts
|

Steam Explosion Pretreatment of Sludge for Pharmaceutical Removal and Heavy Metal Release to Improve Biodegradability and Biogas Production

Abstract: Steam explosion pretreatment was developed and evaluated to remove pharmaceuticals and heavy metals from wastewater sludge and to improve its biodegradability and methane yield. Effects of pressure (5–15 bar) and duration (1–15 min) during the pretreatment were examined, and the pretreatment efficiency was evaluated based on the solubilization degree, the capillary suction time (CST) test and anaerobic digestion. The removal efficiency of ibuprofen, acetaminophen, and amoxicillin was 65%, 69%, and 66% and 70%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…This approach employs high pressure and heat causing break down of sludge structures and contained compounds. The steam explosion eliminates the need for chemical usage; hence, it can be considered as an eco-friendly pretreatment method (Aski et al 2020 ). Aski et al ( 2020 ) confirmed that this method allowed for pharmaceutical and heavy metal removal, such as ibuprofen (in 65 and 69%), acetaminophen (in 66 and 70%), amoxicillin (in 66 and 70%), lead (in 78 and 70%), and cadmium (in 79%) removal from primary sludge and waste-activated sludge by facilitating the leaching them out into the liquid phase.…”
Section: Methods Of Sewage Sludge Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach employs high pressure and heat causing break down of sludge structures and contained compounds. The steam explosion eliminates the need for chemical usage; hence, it can be considered as an eco-friendly pretreatment method (Aski et al 2020 ). Aski et al ( 2020 ) confirmed that this method allowed for pharmaceutical and heavy metal removal, such as ibuprofen (in 65 and 69%), acetaminophen (in 66 and 70%), amoxicillin (in 66 and 70%), lead (in 78 and 70%), and cadmium (in 79%) removal from primary sludge and waste-activated sludge by facilitating the leaching them out into the liquid phase.…”
Section: Methods Of Sewage Sludge Treatmentmentioning
confidence: 99%
“…The steam explosion eliminates the need for chemical usage; hence, it can be considered as an eco-friendly pretreatment method (Aski et al 2020 ). Aski et al ( 2020 ) confirmed that this method allowed for pharmaceutical and heavy metal removal, such as ibuprofen (in 65 and 69%), acetaminophen (in 66 and 70%), amoxicillin (in 66 and 70%), lead (in 78 and 70%), and cadmium (in 79%) removal from primary sludge and waste-activated sludge by facilitating the leaching them out into the liquid phase. Physical pretreatment methods can be applied to sewage sludge pretreatment, as well as reduction of dangerous impact of pharmaceuticals, antibiotics, and heavy metals.…”
Section: Methods Of Sewage Sludge Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…pH is an important factor in bioH 2 production because it affects the activities of enzymes involved in the process [22]. If the pH is too low (acidic), the enzymes responsible for bioH 2 production may become less effective and cause a reduction in bioH 2 production [23]. If the pH is too high (alkaline), the enzymes responsible for bioH 2 production may become inactivated and cause a reduction in bioH 2 production [19].…”
Section: Bioh 2 Productionmentioning
confidence: 99%
“…Several experimental studies were previously performed on biogas containing bioCH 4 and CO 2 from cow dung with waste sludge where only bioCH 4 , CO 2 or volatile solid content was used [20,21]. On the other hand, some other studies only focused on bioH 2 from cattle wastewater [22] and cattle manure [23]. Based on the yield of these earlier studies, the yield of bioCH 4 with CO 2 is higher than bioH 2 , but the energy content of bioH 2 (~120 MJ/kg) is higher than bioCH 4 (~20-30 MJ/kg).…”
Section: Introductionmentioning
confidence: 99%